Assessment of Lecturers and Students’ Preparedness, Readiness and Challenges for Online Education amids Covid-19 Pandemic in Abubakar Tafawa Balewa University Bauchi, Nigeria - Adamu, I. A.; Bala, M. (Kashere Journal of Education, 2021)
The aim of the study is to assess the preparedness, readiness and challenges for online education amid covid-19 pandemic, the study adopted qualitative research and the design used for the study was instrumental case study. The participants were final year undergraduate business education students’ department of vocational and technology education Abubakar Tafawa Balewa University Bauchi. The sampling technique used was purposeful sampling to select six (6) participants, three from the students and three from the academic staff. The researcher with the help of one (1) research assistant conducted face to face interview using semi structured form, with few open-ended questions. Data collected were analyzed using thematic analysis for interview and content analysis for the document. The result of the study revealed that lecturer’s preparedness, readiness and challenges for online education required possession of pedagogical skills to delivered online education using virtual classes and to address fear of cost, fear of acceptance, technophobia and lack of awareness as the impediments hindering online education. It was also revealed that students’ preparedness, readiness and challenges for online education required ability to adapt to changes of moving to online education. The result further revealed that lecturers and student’s preparedness, readiness and challenges required increase in connectivity of network and providing affordable access to network for online education. Based on the findings it was recommended that Government, Private sector, Universities, Non-Governmental organizations and Stakeholders should ensure on the job training of lecturers, sensitization and enlighten of student, supportive programmes, increase wider coverage of internet services and reducing internet charges rate to make it affordable.